Alterations in EGF-Endocytosis, Lysosomal Enzyme Transport and Maturation of Cathepsins in Juvenile Neuronal Ceroid Lipofuscinosis Fibroblasts - Carcel Trullols, Jaime (International Clinical Neuroscience Journal, 2019)
Background: Juvenile neuronal ceroid lipofuscinosis (JNCL), one of the most frequent forms of the NCL storage diseases, is known to be caused by loss-of-function mutations in ceroid-lipofuscinosis neuronal protein 3 (CLN3), but its cell function has not been fully elucidated. We previously reported increased lysosomal pH in CLN3 deficient cells. In the present study, we analysed the consequences of this effect in the endo-lysosomal pathways in CLN3 cells. Methods: The present study investigated different endo-lysosomal pathways in control, CLN2, CLN3 human skin fibroblasts under high and low proteolysis conditions. Cell surface biotinylation after EGF (2 ng/mL) stimulation, EGF phosphorylation (Tyr-845), retromer and cation-independent mannose-6-phosphate receptor (CI-MPR) levels and stability, EGF degradation pathways and cathepsin L and D levels were analysed by western blots. Caveolae mediated endocytosis was analysed by flow cytometry. CIMPR subcellular localization was ascertained by immunocytochemistry, confocal microscopy and further image analysis. Results: Whereas caveolae-mediated endocytosis was not affected in CLN3 cells, clathrin-mediated epidermal growth factor (EGF) internalization was reduced, along with EGF receptor (EGFR) phosphorylation. In addition, cell surface EGFR levels and recycling to the cell membrane were increased. EGFR lysosomal degradation was impaired and our results suggest that the receptor was diverted to proteasomal degradation. We also analysed the machinery responsible for lysosomal hydrolase transport to the lysosome and found increased stability of CIMPR, a major receptor implicated in the transport of hydrolases. The subcellular distribution of the CI-MPR was also altered in CLN3 cells, since it accumulated within the Trans-Golgi network (TGN) and did not progress into the lysosomes. In addition, we found a reduced turnover of retromer subunits, a complex that retrieves the CI-MPR from endosomes to the TGN. Finally and as a possible consequence of these alterations in lysosomal enzyme transport, cathepsin L and D maturation were found suppressed in CLN3 cells. Conclusion: Altogether, these results point to increased lisosomal pH as a pivotal event causing various alterations in intracellular traffic associated to the development of JNCL disease.